Pengaruh Viral Marketing dan Brand Awareness terhadap Niat Beli pada Burger King Indonesia - Dumatri, Agatha Christy Avega; Indarwati, Tias Andarini (Jurnal Ilmu Manajemen, 2021)
Competition for fast food restaurants is so fierce that companies need to find ways to do marketing wisely. Social media is one of the growingÂ platforms that can be used as a marketing medium to reach consumers widely and quickly, which will lead to the emergence of consumer purchase intentions. This study aims to examine the effect ofÂ viral marketingÂ andÂ brand awarenessÂ on purchase intention. This study used 200 respondents with non-probability sampling techniques, and the method used was judgmental sampling were distributed usingÂ onlineÂ questionnaires. Data were analyzed using multiple linear regression. This study found thatÂ viral marketingÂ andÂ brand awarenessÂ have a significant influence on purchase intention â€œBurger King Indonesiaâ€. Based on the result, it can be used as a recommendation â€œBurger King Indonesiaâ€ in increaseÂ brand awarenessÂ more among competitors and have an impact to purchase intention.